Crystal structure and dielectric properties of a new Na2O-Nd2O3-CeO2 ceramic system at microwave frequencies. (February 2018) - Liu, Fei; Qu, Jingjing; Yuan, Changlai; Chen, Guohua
Graphical abstract: Fig. 1 (a) XRD patterns of Na3 x -1 Nd1- x CeO3 (0.4 ≤  x  ≤ 0.6) ceramics sintered at 1300–1400 °C for 2 h, (b) the enlarged figure of (222)/(111) reflection peaks. Highlights: A large amount of Na evaporation can make τf more negative in present ceramics. Na-excess evaporation results in the formation of Ce1- x Nd x O2- x /2 solid solution. Ce1- x Nd x O2- x /2 ( x  = 0.25 and 0.5) solid solutions belong to the same fluorite-type. Abstract: Na2 O-Nd2 O3 -CeO2 ceramic systems of the form Na3 x − 1 Nd1 −x CeO3 ( x  = 0.4, 0.5, and 0.6) were prepared via a solid-state reaction method. X-ray diffraction analyses indicated that the samples with x  = 0.4, 0.6 and those with x  = 0.5 formed Nd0.25 Ce0.75 O1.875 and Nd0.5 Ce0.5 O1.75 solid solutions, respectively, which resulted from a large degree of Na + ion evaporation. Both the Nd0.25 Ce0.75 O1.875 and Nd0.5 Ce0.5 O1.75 phases belonged to the same cubic structure with an Fm-3m (225) space group. Additionally, the microstructures, sintering behaviors, and microwave dielectric properties were considered to be strongly related to the Na content in the Na3 x − 1 Nd1 −x CeO3 ceramics. A relatively large degree of Na + ion evaporation could increase the negative temperature coefficient of the resonant frequency ( τf ) for these ceramic systems. Moreover, after sintering at 1380 °C for 2 h, the x  = 0.6 specimen possessed a low permittivity ( ε r ) of approximately 9.13, a moderate quality factor ( Q  ×  f ) of approximately 23, 800 GHz (at 9.14 GHz) and a negative τf value of approximately −61.7 ppm/°C. As a result, it could be a promising microwave dielectric material for achieving a near-zero τf value by solidifying one or more microwave dielectric ceramics with a high positive τf value.